Analytical Approaches for Detection of a Contaminant with an Emphasis on 3D Dendritic Chip-Based Electrochemical Sensing in Water Samples - Kumari R.; Dkhar D.S.; Chandra P. (My University, 2025)
Water quality has become one of the world's most critical environmental issues. 1,4-dioxane, a hazardous industrial water contaminant produced as a byproduct during the synthesis of ethoxylated surfactants, is a recalcitrant molecule that persists in surface or drinking water for years. In view of its carcinogenicity and ability to pollute water matrices, 1,4-dioxane detection remains an increasingly popular area of investigation. As a result, this study focuses on the detection of 1,4-dioxane using several analytical approaches, the limitations of these approaches, and the advantages of the electrochemical sensing method. In the end, nanoelectronic sensing chips were designed to detect even minute levels of 1,4-dioxane, and subsequently, the capacity to remove 1,4-dioxane is being explored in order to shed light on future research. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.